2003
DOI: 10.1152/ajplung.00395.2002
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular dysfunction in preterm lambs with chronic lung disease

Abstract: Chronic lung injury from prolonged mechanical ventilation after premature birth inhibits the normal postnatal decrease in pulmonary vascular resistance (PVR) and leads to structural abnormalities of the lung circulation in newborn sheep. Compared with normal lambs born at term, chronically ventilated preterm lambs have increased pulmonary arterial smooth muscle and elastin, fewer lung microvessels, and reduced abundance of endothelial nitric oxide synthase. These abnormalities may contribute to impaired respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 63 publications
(65 reference statements)
2
48
0
Order By: Relevance
“…Prolonged MV reduces soluble guanylate cyclase in pulmonary arteries in preterm lambs and a similar phenomenon may occur in preterm infants. 23 It is probable that the physiologic immaturity of the NO signaling pathway and the anatomic immaturity of the vascular smooth muscle are responsible for the lack of response to iNO. The response of preterm infants to iNO parallels the vasodilatory response of pulmonary circulation of fetal lambs to a rise in oxygen tension.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged MV reduces soluble guanylate cyclase in pulmonary arteries in preterm lambs and a similar phenomenon may occur in preterm infants. 23 It is probable that the physiologic immaturity of the NO signaling pathway and the anatomic immaturity of the vascular smooth muscle are responsible for the lack of response to iNO. The response of preterm infants to iNO parallels the vasodilatory response of pulmonary circulation of fetal lambs to a rise in oxygen tension.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in NO sensitivity due to relatively low sGC protein levels may underlie the poor responsiveness seen to inhaled NO in some patients. Indeed, Bland et al (10) found that lambs born prematurely who developed pulmonary hypertension had lower levels of sGC protein and activity than did age-matched controls. In addition, these lambs with pulmonary hypertension demonstrated attenuated responses to inhaled NO compared with age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Both models also recapitulate the pathophysiology and pathology of evolving neonatal CLD in preterm baboons (46,49,50,58,63,124,199) and preterm lambs (5,6,20,24,25,111,139,150). We use the term "evolving neonatal CLD" for the preterm baboon and preterm lamb models and reserve the term "BPD" for preterm human infants, to avoid confusion between large-animal models vs. the human disease.…”
Section: Animal Models As Tools To Identify Pathogenic Mechanisms Leamentioning
confidence: 99%